Christian attitudes toward the Jews in the Middle Ages: a casebook - Frassetto, Michael (Routledge medieval casebooks, 2007)
Conflicting accounts : negotiating a Jewish space in medieval Southern Italy, c. 800-1150 CE / Patricia Skinner -- The cross, the Jews, and the destruction of the Church of the Holy Sepulcher in the writings of Ademar of Chabannes / Daniel F. Callahan -- A great Jewish conspiracy? : worsening Jewish-Christian relations and the destruction of the Holy Sepulcher / Phyllis G. Jestice -- Heretics and Jews in the early eleventh century : the writings of Rodulfus Glaber and Ademar of Chabannes / Michael Frassetto -- Against the enemies of Christ : the role of Count Emicho in the anti-Jewish violence of the First Crusade / Matthew Gabriele -- Abelard and Heloise on Jews and hebraica veritas / Constant J. Mews -- Reason and natural law in the disputational writings of Peter Alfonsi, Peter Abelard, and Yehuda Halevi / Alex Novikoff -- The Jews in the Golden legend / Thomas Renna -- Anti-Jewish attitudes in Anglo-Norman religious texts, twelfth and thirteenth centuries / Maureen Boulton -- Henry II, William of Newburgh, and the development of English anti-Judaism / John D. Hosler -- Jewish witness, forced conversion, and island living : John Duns Scotus on Jews and Judaism / Nancy L. Turner